Formulasi dan Uji Stabilitas Fisik Sediaan Serum Ekstrak Etanol 96% Biji Alpukat (Persea americana Mill) - Rohmanah, Atik; Sari, Gigih Kenanga; Hapsari, Estuningtyas Ayu (Pratama Medika : Jurnal Kesehatan, 2024)
Research on the formulation and physical stability test of 96% ethanol extract serum preparations from avocado seeds (Persea americana Mill). This study aimed to evaluate the physical stability of several serum preparation formulations of avocado seed ethanol extract with different concentrations. The research method was 5 kg of avocado seeds). Experimental research to determine whether 96% ethanol extract of avocado seeds using three concentrations, namely 5%, 7.5% and 10%, could be formulated into a facial serum preparation. This research used a physical stability test method for serum preparations used the cycling test method, which includes organoleptic tests, pH tests, homogeneity tests, viscosity tests, spreadability tests and adhesion tests. The results showed that the secondary metabolite compounds contained in the 96% ethanol extract of avocado seeds were alkaloids, flavonoids, saponins, tannins, steroids or triterpenoids; 96% ethanol extract of avocado seeds could be formulated as a serum preparation, and the stability test results of all serum preparation formulations had good standards for organoleptics, homogeneity, pH, viscosity, spreadability and adhesiveness. The F2 serum preparation (glycerin concentration 7.5%) experienced small changed, so the stability of the F2 serum preparation was better than other preparations. Ethanol extract of avocado seeds could be made into a serum formulation, F2 formulation which had the best physical stability.